Pengaruh Media Pembelajaran terhadap Motivasi Belajar Siswa SMK: Meta Analisis - Zaki, Kaka Ibnu; Iskandar, Ranu; Naryanto, Rizqi Fitri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to evaluate the effect of learning media on the learning motivation of Vocational High School (SMK) students. The method used in this study is a meta-analysis with data collected through Google Scholar and Semantic Scholar in September 2025. The search keywords used Indonesian with a combination of the variables